Event innovativeness towards spectator’s satisfaction and behavioural intention at sport tourism event: Le tour de Langkawi / Mohammad Adzly Rajli - Rajli, Mohammad Adzly (2017)
Malaysia is increasingly and actively promoting itself as an organizer and host to various world-class sports events and recreational activities with the aim of becoming a major sports tourism destination in the Asia-Pacific region (Ministry of Tourism Malaysia, 2014). Nowadays, spectators are quite different from the past. Their needs and demands become higher. Spectators are becoming more sophisticated, discerning and more inclined to complain. Spectators are always expected good quality events provided either from the government sectors or private sectors. This is because spectator's perceptions of experiences provided by the organization are closely related to the loyalty. Spectators nowadays preferred something new that gives them something that 'fresh', creative and innovated experience. Therefore, sport tourism event's organizer needs to add up some innovativeness in their events. Innovation is commonly regarded as adoption of a new idea, information, system, practice, or product (physical goods and services) within the adopting organization or among the customers. Nevertheless, there have been evidently few empirical studies being conducted in exploring the innovativeness in sports tourism events. This study aimed to determine innovativeness at sports tourism event in order to have better execution on the organizing sports tourism event setting. In addition, this study intends to investigate the relationship between event innovativeness, spectator's satisfaction and behavioral intention at sport tourism event focused for Le Tour de Langkawi. The survey adopted Events Innovativeness instruments developed by Yoshida (2009), Yoshida, James & Cronin (2012), which are Innovativeness experience (Offering; Process; Stage and Relationship), Spectator's Satisfaction and Behavioural Intention. Some hypotheses are bring up and tested in a cross-sectional study. To carry out this study, 391 of spectator at sport tourism event were surveyed during Le Tour de Langkawi 2013. The data was collected using the event intercept method and Pearson correlation was applied for data analyses and confirmatory factor analysis (CFA) were performed to reliable the questionnaire. The final results showed that there is significant relationship between innovativeness and spectator's satisfaction. The further findings offer important elements to sport organizers in order to fulfil spectator's demand and attract spectator's behavioural intention toward attending sports tourism events.